Seasonal variations in groundwater quality: A statistical approach - Ali Khan, Mohammad Muqtada; Umar, Rashid; Baten, Md Azizul; Lateh, Habibah; Kamil, Anton Abdulbasah (Academic Journals, 2012)
In this study, a descriptive statistical measure and a partial correlation analysis were applied to groundwater quality data set monitored in pre-monsoon and post-monsoon for three years to investigate seasonal variations of Central Ganga Plain in India. The variables were divided into two categories as “chemical property- HCO3, Cl, SO4, Na, K, Ca, and Mg” and “physical property- electrical conductivity (EC), pH and hardness”. The results revealed that groundwater quality variables (chemical property and physical property) were distinctly different between two seasons. Seasonal changes of groundwater quality caused by ion exchange, dissolution mechanism and anthropogenic influences such as fertilizer, pesticides, agricultural activities, and other industrial units should be taken into consideration by the groundwater managers especially in post monsoon 2005 seasons in which higher concentrations were observed. From the partial correlation coefficient analysis of groundwater samples, dominance of alkalis and relative abundance of SO4during post monsoon were inferred. In the case of the groundwater samples, strong correlation were observed among HCO3 with Cl, SO4, Na, Ca, pH and hardness in the post-monsoon (2005) samples, as well as negative correlation were found among the major variables except HCO3 with Na, Mg, hardness during the pre-monsoon (2006) suggested from partial correlation of groundwater samples.